Ontario Ministry of Natural Resources South-Central Region Bobwhite Quail Rehabilitation Program - P. Hunter; R. Ludolph (National Quail Symposium Proceedings, 2017)
Archaeological and historical evidence on status of northern bobwhites (Colinus virginianus) in southern Ontario prior to European settlement is not clear. The bird was documented on the Essex and Kent County prairies at the time of European settlement in the early l700's. Early farmsteading increased available habitat space for quail. That landscape, combined with mild winters in the l 840's, enabled bobwhites to expand their ranges. By the mid-l 850's, bobwhites ranged generally throughout Ontario's tallgrass prairie and savannah communities extending from the Detroit River approximately 300 miles north into Simcoe County, the southeast limit of Georgian Bay, and 400 miles east to Kingston, the eastern limit of Lake Ontario. Bobwhites became a valued upland bird in pioneer Ontario for hunting, viewing and controlling farm garden weed seeds and insects. The detrimental impacts of harsh winters were a major contributor to quail declines from the late l 850's to the l 980's. Additionally, more subtle factors which also contributed detrimental stresses were loss of tallgrass prairie and savannah, intensive agriculture, continued deforestation, urbanization, pesticide use, the taking of wild stock for pen-rearing and the low survival rates of introduced cultured stocks into the wild. In summary, bobwhites in Ontario declined due to the destruction, impairment and fragmentation of wildlife habitat. The population stabilized at low numbers during the early l 980's. Recreational harvesting of the species continued into the l 970's. Gun harvests probably at no time exerted a controlling influence on the quail populations. The harvest diminished to non-existence in the 1980's. The hunting seasons for wild populations were eliminated in the l 990's. People continued to appreciate the bird for recreational viewing and dog training opportunities. In spite of agricultural trends towards less intensive land uses, new emphases on resource and environmental conservation and rehabilitation, as well as milder winters in the l 980's and l 990's, bobwhite numbers have not rebounded in southwest Ontario. Approximately 185 birds in 16 coveys throughout Elgin, Lambton and Middlesex counties were documented in 1990. Although large areas of suitable land are unoccupied by bobwhites, populations remain small, disjunct and isolated. Ontario Ministry of Natural Resources formed partnerships with a number of other governmental agencies, non-governmental organizations and landowners, to initiate the rehabilitation of bobwhite quail in southern Ontario. The Ontario Federation of Anglers and Hunters, their affiliate and individual members, are a key sponsor to this rehabilitation initiative. These groups have participated in an advisory committee, raised funds, and offered volunteer labor, predator control services adjacent to release sites, and professional services. The committee recommended the transfer of wild bobwhites from other North American populations as a means of rehabilitating Ontario populations. The program's goal is to reestablish larger, sustainable populations of quail in southern Ontario to provide recreational viewing and hunting opportunities. It is anticipated that large numbers of urban and rural Ontarians will be pleased with the reestablishment of northern bobwhites and the recreational viewing and hunting benefits they provide. Restoration of quail hunting opportunities will generate economic benefits in Ontario and may be a suitable method for monitoring the grass-shrubland ecotone. Healthy quail populations also have the potential to function as natural control agents for some crop pests.